2021
DOI: 10.3390/diagnostics11111948
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Assessment of Three-Dimensional Choroidal Vascularity and Choriocapillaris Flow Signal Voids in Myopic Patients Using SS-OCTA

Abstract: Purpose: To compare the choroidal vascularity of large- and middle-sized choroidal vessels and choriocapillaris (CC) perfusion in patients with different degrees of myopia using swept-source optical coherence tomography angiography (SS-OCTA). Methods: One hundred and thirteen people with myopia were enrolled. SS-OCTA was performed to analyze the choroidal vascularity and CC perfusion. Three-dimensional (3D) choroidal vascularity index (CVI) and choroidal luminal volumes (LV) were obtained by artificial intelli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 30 publications
4
14
1
Order By: Relevance
“…The CVI and CVV were also shown to be statistically decreased in the myopia groups. These results were also consistent with previous studies [34][35][36][37][38] . However, though a variation of FAZ in myopia group was noted, there was no significant correlation between the parameters and refractive error or AL in the regression analysis.…”
Section: Discussionsupporting
confidence: 93%
“…The CVI and CVV were also shown to be statistically decreased in the myopia groups. These results were also consistent with previous studies [34][35][36][37][38] . However, though a variation of FAZ in myopia group was noted, there was no significant correlation between the parameters and refractive error or AL in the regression analysis.…”
Section: Discussionsupporting
confidence: 93%
“…As for the controversial results of choroidal vascularity and CVI, Yazdani et al (2021) found that 2D CVI was larger in the myopic group than in the emmetropic group (range: 20–38 years), which is contrary to our result. However, Wu et al (2021) and Xu et al (2021) showed a negative correlation between CVI and AL. The former study indicated that topographic changes in 2D CVI were prominent in the temporal and inferior macular regions, with an age range of 20–27 years.…”
Section: Discussionmentioning
confidence: 82%
“…Similar findings were also reported by Panda-Jonas et al (2021) and Su et al (2020) . Very recently, Xu et al (2021) found that 3D CVI and blood perfusion of CC decreased with increasing severity of myopia.…”
Section: Discussionmentioning
confidence: 98%
“…Using swept-source optical coherence tomography angiography, a gradual decrease in choroidal vascularity with myopia severity has been reported ( 48 ). Decreased choriocapillaris blood flow was associated with thinner choroid and increasing myopia severity ( 48 ). This suggests that the oxygen supply to the sclera may possibly be reduced.…”
Section: Discussionmentioning
confidence: 99%